2013
DOI: 10.3807/josk.2013.17.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Optical Tissue Clearing Laser Probe System

Abstract: Although low-level laser therapy (LLLT) has been a valuable therapeutic technology in the clinic, its efficacy may be reduced in deep tissue layers due to strong light scattering which limits the photon density. In order to enhance the photon density in deep tissue layers, this study developed an optical tissue clearing (OTC) laser probe (OTCLP) system which can utilize four different OTC methods: 1) tissue temperature control from 40 to 10℃; 2) laser pulse frequency from 5 to 30 Hz; 3) glycerol injection at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The temperature dependency of the Grüneisen parameter has previously been explored in several studies [8,[10][11][12][13][14][15][16][17][18]20]. There are also studies showing the temperature dependency of the scattering coefficient of the tissue [19][20][21][22][23][24]. There is not sufficient evidence about how the absorption coefficient of tissue alters with temperature, particularly in the range of temperature investigated in our study [22][23][24].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The temperature dependency of the Grüneisen parameter has previously been explored in several studies [8,[10][11][12][13][14][15][16][17][18]20]. There are also studies showing the temperature dependency of the scattering coefficient of the tissue [19][20][21][22][23][24]. There is not sufficient evidence about how the absorption coefficient of tissue alters with temperature, particularly in the range of temperature investigated in our study [22][23][24].…”
Section: Introductionmentioning
confidence: 71%
“…Troy et al reported a positive scattering coefficient change for prostate tissue [22]. Yeo et al studied the porcine and found an increase in the scattering coefficient with the temperature rise [20].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used approach is replacing interstitial fluids (RI~1.33) in inter-and intra-cellular space with optical clearing agents (OCAs) which have refractive indices of ~1.46, matched to the average refractive index of most biological samples. It has been demonstrated that several OCAs such as glycerol [26- [30][31][32] and BABB [33] can enhance imaging depth in various organs such as brain [22][23][24][25][26], skin [27][28][29], pancreas [30], colon [31] and heart [32][33][34]. However, optical clearing effect of OCAs on LN has not yet been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…For the last decade, optical clearing technique to improve the imaging depth has been actively investigated [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. As the mismatch in refractive index (RI) between cellular components in tissue is the major cause of light scattering, selective removal of cellular components with relatively low or high refractive index can reduce the light scattering and make the tissue more optically transparent.…”
Section: Introductionmentioning
confidence: 99%